Is magnetic resonance imaging teratogenic during pregnancy? literature review (2017)
Magnetic resonance imaging is a diagnostic tool used for obtaining an image through the combination of electromagnetic fields and radiofrequency. Given its properties and safety, it is the imaging modality of choice in pregnant women. However, little is k